Effect of consumption of cookies made with Andean crops on biochemical indicators in recently weaned Wistar rats - Paulina Valdivia Barra, Tatiana; Flores de Quispe, Tita; Reynaldo Paredes Quispe, Juan; Guillermo Apaza Ahumada, Moises (Edelweiss Applied Science and Technology, 2024)
Andean crops such as quinoa, cañihua and tarwi have high nutritional value; however, their consumption has lower demand compared to traditional cereals such as wheat, rice, barley and soybean. Therefore, the aim is to evaluate the effect of its incorporation in the diet on biochemical indicators in Wistar rats. The research had a quantitative approach, descriptive type, using an experimental design and establishing 24 rats as sample size. There was a control treatment composed of wheat only, and three that contained 50% of wheat flour and the remaining quinoa, cañihua and tarwi flour. With the Andean crops, HDL levels were increased, while LDL levels tended to decrease concerning the wheat treatment; likewise, with the Andean cereals, the glucose level was maintained at optimal standards, and there was also an increase in hemoglobin and hematocrit. It concludes that the intake of products made from Andean crops has a positive effect on the body, increasing HDL levels, hemoglobin and hematocrit levels and decreasing or attenuating glucose concentrations in the blood, which is essential for proper health.